2013
DOI: 10.1093/jjco/hyt003
|View full text |Cite
|
Sign up to set email alerts
|

Oncology Nurses' Recognition of Supportive Care Needs and Symptoms of their Patients Undergoing Chemotherapy

Abstract: Objective: To assess the accuracy of oncology nurses' recognition of supportive care needs and symptoms of their patients undergoing chemotherapy. Methods: The participants comprised randomly selected cancer outpatients receiving chemotherapy in an ambulatory setting and 17 oncology nurses working in two chemotherapy units in Japan. For assessment of the patients' supportive care needs and symptoms, the patients were asked to respond to a validated self-administered questionnaire. The oncology nurses completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 35 publications
2
17
0
9
Order By: Relevance
“…The women in this study had high unmet supportive care needs, with unmet needs greatest in the health system and information, and physical and daily living domains. This is similar to Asian studies conducted in Taiwan (Liao et al, 2012), Japan (Nakaguchi et al, 2013) and Hong Kong Li et al, 2013) wherein breast cancer patients reported high rates of unmet supportive care needs, particularly in the informational domain. This contrasts with research conducted in Western countries, including Switzerland (Schmid-Büchi et al, 2012), Australia (Hodgkinson et al, 2007;McDowell et al, 2010), Germany (Lam et al, 2011), England (Armes et al, 2009;Harrison et al, 2011) and Canada (Whelan et al, 1997), wherein breast cancer patients have moderate levels of supportive care needs and unmet needs were highest in the psychological domain.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The women in this study had high unmet supportive care needs, with unmet needs greatest in the health system and information, and physical and daily living domains. This is similar to Asian studies conducted in Taiwan (Liao et al, 2012), Japan (Nakaguchi et al, 2013) and Hong Kong Li et al, 2013) wherein breast cancer patients reported high rates of unmet supportive care needs, particularly in the informational domain. This contrasts with research conducted in Western countries, including Switzerland (Schmid-Büchi et al, 2012), Australia (Hodgkinson et al, 2007;McDowell et al, 2010), Germany (Lam et al, 2011), England (Armes et al, 2009;Harrison et al, 2011) and Canada (Whelan et al, 1997), wherein breast cancer patients have moderate levels of supportive care needs and unmet needs were highest in the psychological domain.…”
Section: Discussionsupporting
confidence: 83%
“…Investigations of supportive care needs among South East Asian breast cancer patients suggests that a large percentage have unmet needs Liao et al, 2012;Au et al, 2013;Li et al, 2013;Nakaguchi et al, 2013). Previous Iranian researchers have documented high rates of disrupted psychological functioning among breast cancer patients (Montazeri et al, 2002;Tavoli et al, 2008), and a lack of disease and treatment related information or education (Montazeri et al, 2002), but evidence of unmet supportive care needs is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Depression in cancer patients can interfere with treatment and recovery and may subsequently increase their morbidity and mortality. 22 In the present study, the proportion of depression was found to be quite high (73.69%) as compared to most of the other studies conducted by Bhattacharyya 6,16,23,24 However, similar findings were reported by Jadoon et al who found the prevalence of depression to be 66%. 25 In the present study significantly higher proportion of depression can be attributed to greater number of female study subjects who are usually willing to express depression and tend to apply emotional approach for coping.…”
Section: Discussionsupporting
confidence: 81%
“…Social support and a better functional status encourage patients with cancer to engage in more self-care behaviours for the management of fatigue (Lou et al, 2013). A study involving patients with breast, colorectal and lung cancer found that assessments of psychological symptoms and social support were considerably neglected by nurses (Nakaguchi et al, 2013). A multicentre study reported that less social support and high levels of symptom distress during chemotherapy were associated with worse QoL in patients with breast cancer receiving chemotherapy or radiotherapy (So et al, 2009).…”
Section: Relationship Between Qol Scores and Level Of Fatiguementioning
confidence: 99%